2006
DOI: 10.1128/aac.01411-05
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Mammalian Mitochondrial Protein Synthesis by Oxazolidinones

Abstract: The effects of a variety of oxazolidinones, with different antibacterial potencies, including linezolid, on mitochondrial protein synthesis were determined in intact mitochondria isolated from rat heart and liver and rabbit heart and bone marrow. The results demonstrate that a general feature of the oxazolidinone class of antibiotics is the inhibition of mammalian mitochondrial protein synthesis. Inhibition was similar in mitochondria from all tissues studied. Further, oxazolidinones that were very potent as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
183
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(194 citation statements)
references
References 38 publications
9
183
1
1
Order By: Relevance
“…Chloramphenicol, a ribosomal antibiotic that binds to the peptidyl transferase center in the bacterial ribosome, 14 is known to impair protein synthesis in isolated rat heart mitochondria. 7 Our results from the HCS assay showed that the macrolides, erythromycin (Fig. 3C), azithromycin, and telithromycin, did not impair Complex IV-subunit 1 levels in THLE-2 cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Chloramphenicol, a ribosomal antibiotic that binds to the peptidyl transferase center in the bacterial ribosome, 14 is known to impair protein synthesis in isolated rat heart mitochondria. 7 Our results from the HCS assay showed that the macrolides, erythromycin (Fig. 3C), azithromycin, and telithromycin, did not impair Complex IV-subunit 1 levels in THLE-2 cells.…”
Section: Discussionmentioning
confidence: 97%
“…7 Nagiec et al 6 have shown, by Western blotting, that linezolid decreases Complex IV-subunit 1 levels in human erythroleukemia cells. The decrease in Complex IV-subunit 1 seen in linezolid-treated THLE-2 cells in our HCS assay is in accord with these results.…”
Section: Discussionmentioning
confidence: 99%
“…14,19 Interestingly, the mean half-maximal inhibitory concentration of linezolid against mitochondrial protein synthesis (IC50) in rat and rabbit heart and liver mitochondria was 4.31 mg/L. 20 Accordingly, it may be reasonably supposed that linezolid-induced thrombocytopenia might occur more frequently among patients who have linezolid plasma concentrations above this threshold value for the entire dosing interval. 21 Of the 30 patients 10% patients showed marked decrease in haemoglobin value when compared from baseline to subsequent weeks till 21days, these events may be drug related as the linezolid plasma concentration (Cmin) was found more in those patients too.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1, meclocycline and minocycline significantly inhibit cellular proliferation when combined with ATO, compared to either agent alone, in both SK-Mel-19 and M-14 melanoma cells. Because previous studies showed that the antiproliferative effects of tetracyclines in certain mammalian cells results from binding to, and inhibition of, mitochondrial ribosomes (28), we hypothesized that the sensitization to ATO was due to inhibition of mammalian mitochondrial protein synthesis by the tetracyclines (18).…”
Section: Tetracyclines and Thiostrepton Enhance Ato-mediated Growth Imentioning
confidence: 99%